2014
DOI: 10.1021/jz5005335
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-Dependent Full-Color Emission Tunability in a Flexible Carbon Dot Ionogel

Abstract: Multicolor luminescent materials are of immense importance nowadays, while it still constitutes a challenge to achieve luminescence color tunability, transparency, and flexibility at the same time. Here we show how ultrasmall carbon dots (CDs) fluorescing strongly across the visible spectrum can be surface functionalized and incorporated into highly flexible hybrid materials by combination with ionic liquids within silica gel networks to form CD-ionogels with properties promising for fabrication of flexible di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
279
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 382 publications
(293 citation statements)
references
References 53 publications
13
279
0
1
Order By: Relevance
“…In Figure 2 The optical properties of Silica/F127-CDs were studied by means of UV-Vis ( Figure 4) and photoluminescence (PL) spectroscopies ( Figure 5). As demonstrated in Figure 4(line b), Silica/F127-CDs showed strong optical absorption (OA) in the UV region with two absorption bands centered at 241 nm (π-π* transition) and 363 nm (n-π* transition) [28], with full widths at half maximum (FWHM) of 79.9 and 32.5 nm, respectively, where in the reference spectrum of pristine mesoporous material no such peaks are observed in the whole UV-Vis range (see Figure 4 line a). The absorption spectrum, of the heat treated Silica/CDs (see Figure 4 line c) shows a broad featureless absorption profile, however, with some minor characteristic features at 300nm that have been blue shifted from the 363nm peak.…”
Section: Resultsmentioning
confidence: 96%
“…In Figure 2 The optical properties of Silica/F127-CDs were studied by means of UV-Vis ( Figure 4) and photoluminescence (PL) spectroscopies ( Figure 5). As demonstrated in Figure 4(line b), Silica/F127-CDs showed strong optical absorption (OA) in the UV region with two absorption bands centered at 241 nm (π-π* transition) and 363 nm (n-π* transition) [28], with full widths at half maximum (FWHM) of 79.9 and 32.5 nm, respectively, where in the reference spectrum of pristine mesoporous material no such peaks are observed in the whole UV-Vis range (see Figure 4 line a). The absorption spectrum, of the heat treated Silica/CDs (see Figure 4 line c) shows a broad featureless absorption profile, however, with some minor characteristic features at 300nm that have been blue shifted from the 363nm peak.…”
Section: Resultsmentioning
confidence: 96%
“…This is because RET competes with radiative transition and then shortens the lifetime. [ 3 ] Besides, excitation dependence is also one of the key factors for signifi cant wavelength-shift of CDs demonstrated by a previous report, [ 22 ] because it can further strengthen the long wavelength of emission after the re-absorption process ( Figure S4, Supporting Information). As a consequence of this property, the aggregated NCD has a larger red-shift than crystalline organic molecules which are excitation independent.…”
Section: Communicationmentioning
confidence: 84%
“…With the above phenomena and according to the spectral overlap between absorption and emission, which is usually described in terms of the Förster distance ( R 0 ) for convenience (Figure 2 d), it is believed that the extra-large red-shift are ascribed to RET or re-absorption, which always occurs in small interparticle distance less than R 0 . [ 3,22 ] The probable mechanism of the large red-shift in the solid state is that the short wavelength of emission that overlaps the absorption (340−500 nm) is weakened due to the energy transfer, and, as a consequence, the long one is comparatively strengthened. To verify the RET happening in NCD 220 aggregates, the fl uorescence decay curves (Figure 2 e) of NCD 220 aqueous solution and powder were measured.…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the formation of gels based on carbon-based nanodots had been reported [20][21][22][23][24], but few analytical applications had been described until now. Quaranta et al reported the formation of a thin xerogel film of carbon-based nanodots to scintillators detectors and Hu et al used Carbon Dot Gels (CDGs) as part of a sensing system for the direct detection of Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%